2017
DOI: 10.13057/nusbiosci/n090119
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The clay nanoparticle impregnation for increasing the strength and quality of sengon (Paraserianthes falcataria) and white meranti (Shorea bracteolata) timber

Abstract: Abstract. Alex T, Winarni B, Kusuma IW, Arung ET, Budiarso E. 2017. Short Communication: The clay nanoparticle impregnation for increasing the strength and quality of sengon (Paraserianthes falcataria) and white meranti (Shorea bracteolata) timber. Nusantara Bioscience 9: 107-110. The clay nanoparticle impregnation for increasing the strength and quality of sengon (Paraserianthes falcataria) and white meranti (Shorea bracteolata) timber. The clay nanoparticles as a fine particle material dissolved in water wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The pit membranes were not aspirated as this would completely seal off any liquid transport between the lumen and would therefore hinder the impregnation drastically. Comparison to previously published studies is difficult, since either particles with different particle sizes [27,44,45] or very broad particle size distributions [14,46,47] are reported, which makes it impossible to unambiguously define particle size thresholds. In our study, we observed a much lower size limit for particle impregnation in pine wood impregnation than the reported 400-600 nm.…”
Section: Impregnation Of Pine Woodmentioning
confidence: 93%
“…The pit membranes were not aspirated as this would completely seal off any liquid transport between the lumen and would therefore hinder the impregnation drastically. Comparison to previously published studies is difficult, since either particles with different particle sizes [27,44,45] or very broad particle size distributions [14,46,47] are reported, which makes it impossible to unambiguously define particle size thresholds. In our study, we observed a much lower size limit for particle impregnation in pine wood impregnation than the reported 400-600 nm.…”
Section: Impregnation Of Pine Woodmentioning
confidence: 93%